Withania somnifera: Advances and Implementation of Molecular and Tissue Culture Techniques to Enhance Its Application - Pandey, Vibha; Ansari, Waquar Akhter; Misra, Pratibha; Atri, Neelam (Frontiers in Plant Science, 2017)
Withania somnifera, commonly known as Ashwagandha an important medicinal plant largely used in Ayurvedic and indigenous medicine for over 3,000 years. Being a medicinal plant, dried powder, crude extract as well as purified metabolies of the plant has shown promising therapeutic properties. Withanolides are the principal metabolites, responsible for the medicinal properties of the plant. Availability and amount of particular withanolides differ with tissue type and chemotype and its importance leads to identification characterization of several genes/ enzymes related to withanolide biosynthetic pathway. The modulation in withanolides can be achieved by controlling the environmental conditions like, different tissue culture techniques, altered media compositions, use of elicitors, etc. Among all the in vitro techniques, hairy root culture proved its importance at industrial scale, which also gets benefits due to more accumulation (amount and number) of withanolides in roots tissues of W. somnifera. Use of media compostion and elicitors further enhances the amount of withanolides in hairy roots. Another important modern day technique used for accumulation of desired secondary metabolites is modulating the gene expression by altering environmental conditions (use of different media composition, elicitors, etc.) or through genetic enginnering. Knowing the significance of the gene and the key enzymatic step of the pathway, modulation in withanolide contents can be achieved upto required amount in therapeutic industry. To accomplish maximum productivity through genetic enginnering different means of Withania transformation methods have been developed to obtain maximum transformation efficiency. These standardized transformation procedues have been used to overexpress/silence desired gene in W. somnifera to understand the outcome and succeed with enhanced metabolic production for the ultimate benefit of human race.